Concurrent validity, inter-unit reliability and biological variability of a low-cost pocket radar for ball velocity measurement in soccer and tennis - Hernández-Belmonte, A.; Sánchez-Pay, A. (Journal of Sports Sciences, 2021)
This study aimed to analyse the (i) concurrent validity, (ii) inter-unit reliability, and (iii) biological variability of a low-cost device called Pocket radar. Eleven men recreational soccer players performed 6 kicks to a soccer ball, whereas 13 men recreational tennis players conducted 10 shots to a tennis ball. All executions were simultaneously measured by two Pocket units and the Stalker radar (reference criterion). The within-subject variation among the executions was used for the biological variability analysis. The level of agreement and magnitude of errors included the intraclass correlation coefficient (ICC), Pearson`s correlation coefficient (r), bias, and the smallest detectable change (SDC). A good agreement (ICC = 0.98, r = 0.98) and very low magnitude of error (SDC = 7.70 km/h, bias = 3.19 km/h) were found between both Pocket units and the Stalker, in soccer and tennis. Inter-unit analysis found limited technical errors (SDC = 5.49 km/h, bias = -0.93 km/h) and nearly perfect agreement (ICC = 0.99, r = 0.98) in both sessions. These technical errors were lower than the variations due to the biological variability, in soccer (SDC = 2.47 km/h vs. SDC = 8.6 km/h) and tennis (SDC = 5.49 km/h vs. SDC = 21.95 km/h). These findings suggest the Pocket radar as a valid and highly sensitive tool for BV measurement.